The Ability to Manage Unexpected Events and the Vocational Identity in Young People: The Italian Validation of Planned Happenstance Career Inventory - Sica, Luigia Simona; Ponticorvo, Michela; Di Palma, Tiziana (Frontiers in Psychology, 2022)
The purpose of the present study was to test the validity of Planned Happenstance Career Inventory (PHCI) also in the Italian context with a sample of 476 undergraduate students attending university in the southern of Italy. Moreover, we examined relationships between the PHCI and measures of vocational identity processes. Also, for the Italian version of the instrument was confirmed a multifactor structure in line with the original version. The results show convergent and divergent validity of the measure. Finally, the skills of planned happenstance show different associations with Vocational Identity Dimensions. As hypothesized, the exploration and commitment dimensions of vocational identity status are positive related to Planned Happenstance Skills. These findings suggest implications for career guidance and counselling.